Construction and Application for Operation-BusinessOriented Mobile GIS Service Platform - Jia Wu; Dan Su; Wang Li; Weiguo Yuan; Rui Yang (Dianxin kexue)
Transport inspection services for mobile applications using fu11 text office mode，mobile applications cannot achieve the graphical visualization of GIS management. Therefore，based on geographic information system，GPS and wireless communications technology，a unified mobile GIS application platform was constructed. The platform uses the mobile GIS spatial data security encryption technology，power navigation map engine technology，navigation path analysis techniques. The platform was used to asset management of transport inspection service，equipment inspection，fault repair，defect management. The platform effectively improves the efficiency of mobile operating and the management of transport inspection.